Introduction to the Environment and Workflow through the Implementation of the FIFO Program and Modernization in Wholesale Store Operations at PT. Indomarco Prismata Di Indogrosir Kemayoran Branch - Phymendyta Aldaning Azaria; Patricia Christie Watulangkou (Budapest International Research and Critics University, 2022)
To meet the needs of the community in this segment, PT. Indomarco Prismatama formed a company, namely PT. Inti Cakrawala Citra, also known as Indogrosir. PT. Inti Cakrawala Citra is a company that does business in the wholesale or wholesale sector and has spread throughout Indonesia. This company has experience since 1993 with the vision of “Being a national asset in a modern distribution network that excels in global competition” and has a mission of “generating and developing entrepreneurs in the retail sector”. Indogrosir continues to grow by maximizing the needs of the community, especially small traders with the motto